Review of the fur-mite genus Soricilichus Fain, 1970 (Acariformes: Chirodiscidae)—symbionts of the African shrews of the subfamily Crocidurinae (Soricomorpha: Soricidae) - Bochkov, Andre V.; Mbalitini, Sylvestre G.; Verheyen, Erik (Zootaxa, 2016)
The fur-mite genus Soricilichus Fain, 1970 (3 species) (Acariformes: Chirodiscidae) represented by permanent symbionts of the African shrews of the subfamily Crocidurinae (Soricomorpha: Soricidae) is revised. The external morphology of these species was investigated with light and scanning electron microscopy. Based on the type specimens and newly obtained samples, 2 recognized species, S. scutisorex Fain, 1970 from Scutisorex somereni Thomas and S. kivuensis Fain, 1981 from Crocidura sp.—both are from DR of Congo—are redescribed. A new species S. sylvisorex sp. nov. found on shrews of the genera Sylvisorex (S. granti Thomas (type host), S. lunaris Thomas, S. vulcanorum Hutterer and Verheyen) and Crocidura (C. denti Dollman, C. cf. niobe, Crocidura sp.), collected in the DR Congo is also described. An amended generic diagnosis, including description of female immature stages, and a key to species are provided.